(3cJGH GdWH GdfHhis
(3ChdgG (B:s
(3GdMeO ddg GdcGai hHYO aEf GdEYJOGd ai GdCHOGf HefRdI GdEfSGf ai GdEfSGf afXQfG ai CUd gh GdYeOI ai GdWH GdfHhi s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg aEf GdeYGdL GdMGPb jYed eG jfHZi Ke jJhcd Ydi Gddg JYGdi ai fLGMg cPdc GdadGM jMQK hjHPQ Ke jJhcd Ydi Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs